Physical chemistry - Levine, Ira N. (McGrae Hill Education (India) Private Limited, 2002)
The sixth edition of Physical Chemistry provides students with an in-depth fundamental treatment ofphysical chemistry. At the same time, the treatment is made easy to follow by giving full step-by-stepderivations, clear explanations and by avoiding advanced mathematics unfamiliar to students. Necessarymath and physics have thorough review sections. Worked examples are followed by a practice exercise.
Index 967-989p.